LITERARY WORKS AS THE MOST IMPORTANT AND WELL-ACCLAIMED COMPONENTS OF THE CULTURAL HERITAGE OF THE NATION - Abdullaev, Ulmasbek (Ижтимоий-гуманитар фанларнинг долзарб муаммолари / Актуальные проблемы социально-гуманитарных наук / Actual Problems of Humanities and Social Sciences., 2024)
This article delves into the multifaceted realm of literary work, emphasizing its traditional, oral, and communal nature. It explores the diverse components of folklore encompassing beliefs, customs, expressions, and practices shared within various cultural groups. The piece highlights the dynamic nature of folklore, which evolves through repetition, variation, and adaptation while retaining significance and continuity for the collective identity of communities. Through the lens of various folklorists' perspectives, it challenges stereotypes and misconceptions about folklore, portraying it as a living, integral aspect of contemporary life across different cultural landscapes. The article underscores the significance of folklore in preserving cultural heritage, fostering collective identity, and illuminating the universal human experience.